„Professionality, quality, effectivity, community”: Interview with Dr. Gábor Kovács, pol. brigadier-general, dean of the Faculty Law Enforcement at the University of Public Service (Academic Journal of Internal Affairs, 2021)
From 16th July 2021 is Dr. Gábor Kovács, pol. brigadier-general, the dean of the Faculty Law Enforcement at the National University of Public Service. He began his work as dean with experiences of decades in his positions as university lecturer, department leader and deputy rector. He is secretary general of the Hungarian Association of Police Science and member of the Professional Advisory Board of Belügyi Szemle. His speciality is border policing, law enforcement education, leadership and organisation theory, leadership theory in law enforcement. In these topics several publications of him were released. According to his self-declaration he has undergone each grade as police professional and as educator. With considerable experiences he is always ready for new development and necessary changes. Beside safeguarding the conditions for a qualitative education for law enforcement officers he intends to make the faculty and the weekdays at the university tenderly for the students. We asked Dr. Gábor Kovács about his expectations and plans when he began leading the Faculty Law Enforcement, and what he means about present and future of law enforcement education.
Keywords: interview; public service; higher education; officer training